The unusual toxicity and stability properties of crude venom from isolated nematocysts of Pelagia noctiluca (Cnidaria, Scyphozoa) - Marino, A.; Crupi, R.; Rizzo, G.; Morabito, R.; Musci, G.; La Spada, G. (Cellular and Molecular Biology, 2007)
We have firstly investigated the toxicological activity by hemolytic assay of crude extract obtained by sonication of holotrichous isorhiza isolated nematocysts of the Scyphozoan Pelagia noctiluca, collected in the Strait of Messina. The hemolytic activity was both time- and dose-dependent on fish, rabbit, chicken and human red blood cells. At lowest doses rabbit and chicken erythrocytes were the most sensitive, whereas those of eel were the most resistant to the crude extract. Different storage conditions, such as -20 degrees C, -80 degrees C for up to 6 months and lyophilization, did not affect the stability of crude venom. Moreover, neither treatment at 4 degrees C, 20 degrees C and 37 degrees C for different time periods ranging between 30 min and 24 h, nor harsh thermal treatment at 80 degrees C and 100 degrees C affected the hemolytic power. The crude venom resulted even stable towards proteolysis and alkaline pH values.